A study of perceptions of mothers, caregivers, and school-age children regarding educational experiences during maternal army reserve component deployments - Custer, Kristy (Kansas State University, 2014)
The purpose of this study was to gain better insight into the perceptions of mothers, caregivers, and school-age children in regard to educational experiences (defined as social, academic, and behavioral by Kansas Department of Education, 2012) during maternal Army Reserve component deployments. Since the September 11, 2001, attacks on the World Trade Center, reserve component deployments have become an integral part of the total military strategy. Because the reserve component could be trained and equipped for a fraction of the active forces, fiscal realities dictated moving routine operational responsibilities to the reserve component (National Guard and Reserve Equipment Report for 2013, 2012). As more citizen soldiers were called to active duty deployments, the effects on children who did not typically identify with being in a military family were particularly important to their well-being. This qualitative case study looked at perceptions regarding maternal reserve component deployments through the theoretical perspective lens of ambiguous loss and boundary ambiguity. “Ambiguous Loss Theory” was a type of family stress termed by Boss (1999) that identified the loss or absence of a family member or loved one that evoked emotional uncertainty and ambiguity in the family (p. 7). “Boundary Ambiguity” was how the family interpreted or perceived the situation of ambiguous loss (Boss, 2002). Research applying Boss’ Ambiguous Loss Theory showed that deployment of a family member in a military family was a major stress factor for military children and caused emotional uncertainty and ambiguity in the family (Faber, Willerton, Clymber, Macdermid, & Weiss, 2008; Huebner, Mancini, Wilcox, Grass & Grass, 2007). As mothers were still recognized as the primary caregivers of children in the United States (Galinsky, Aumann, & Bond, 2011), the absence of a mother due to deployment significantly shifted responsibilities not only to the new primary caregiver, but children also took on new responsibilities as well. Role ambiguity began prior to the deployment, continued during the deployment, and could have the most overwhelming effects post-deployment as family members reintegrated the deployed parent back into the family (Huebner et. al, 2007). Utilizing a qualitative multiple case study, the research was conducted from a social constructivist worldview. Criterion sampling was used to garner four total cases for the study Data from both interviews and documents were collected. The purpose of this study was to gain better insight into the perceptions of mothers/soldiers, caregivers, and school-age children regarding their roles in the educational experiences (defined as social, academic, and behavioral by Kansas Department of Education, 2012) during maternal Army Reserve component deployments. Based on the data, six themes emerged that addressed the overarching research questions of this study: • When deployed mothers/soldiers did not maintain a role in the child’s educational experiences, families perceived role definitions as difficult to establish. • Communication during deployment was a key factor in establishing roles of mother/soldier, child, and caregiver. • Clearly defined roles in educational experiences of the child were a key factor in reintegration. • Schools were perceived as a resource to families experiencing deployment. • Children perceived their roles as maintaining or improving their educational experiences as ways to support mother/soldier during deployment. • When roles in children’s educational experiences were not clearly defined, children perceived stress.
Keywords: Reserve component; Ambiguous loss; Boundary ambiguity; Deployment; Education; Maternal; Educational Administration (0514); Educational leadership (0449); Education, General (0515)